The relationship between pastoral care and worship in the context of HIV/AIDS : a study of the development and impact of the liturgical material 'Worship and HIV/AIDS' in selected parishes of the Diocese of Cape Town - Griffiths, Keith Leonard (Stellenbosch : Stellenbosch University, 2011)
Thesis (MTh)--Stellenbosch University, 2006.